Pengaruh Keterlibatan dan Kesejahteraan terhadap Kinerja Karyawan di PT. Putra Indo Mandiri Sejahtera Sumatera Utara - Br Ginting, Elfrika Suka Indah; Rizky, M. Chaerul; Br Bukit, Eka Novita; Wahyuni, Nana (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
In today’s competitive business environment, enhancing employee performance has become a strategic priority for organizations seeking long-term sustainability. Companies are increasingly recognizing that employee performance is not solely driven by technical skills or productivity targets, but also by psychological and emotional factors such as engagement and well-being. This study aims to analyze the impact of employee engagement and well-being on performance at PT. Putra Indo Mandiri Sejahtera (PIMS), an agribusiness company specializing in integrated livestock farming and dairy processing. A quantitative approach was employed, supported by qualitative insights, to provide a comprehensive understanding of the research problem. Data were collected from 51 employees through structured questionnaires and in-depth interviews. Multiple linear regression analysis was used to test the relationships among the variables. The findings reveal that both engagement and well-being have a positive and significant influence on employee performance, with engagement playing a more dominant role. These results underscore the critical role of human resource strategies that not only focus on increasing output but also foster employee involvement and psychological welfare. Investing in engagement and well-being initiatives can be a key driver in improving overall performance and sustaining competitive advantage in the agribusiness sector.